Anotaciones marginales a un poema de Antonio de Nebrija // Marginalia to a Poem by Antonio de Nebrija - Daniel Río Lago (Translat Library, 2023)
This paper examines Latin marginalia found in an elegiac poem composed by Antonio de Nebrija as a paratext to his edition of Prudentius, printed by Arnao Guillén de Brocar (Logroño, 1512). Additionally, this paper aims to make known a valuable copy of the edition that is kept in the Biblioteca Menéndez Pelayo in Santander (sig. 30).